Letter (copy) - Harries, E. P.
037-0029-001 FEA/255 Organisation 13th October, 1937. Miss B.L. Arne, Basque Children's Committee, 53, Marsham Street, S.W.1. Dear Miss Arne, EDUCATION OF BASQUE CHILDREN. Thank you for the letter of yesterday giving me the information regarding the ages of the Basque boys who are at present in England. On the question of the education of these boys, I attach herewith copy of a letter which I have today sent to Dr. Thomas Jones, C.H., of the Pilgrim Trust. Yours sincerely, Secretary, Organisation Department. Copy of letter. 292/946/37/29